Current and Emerging Ethical Issues in Marketing New Directions and Proposals (Global Journal of Management and Business Research, 2013)
The intention of this article is to set up the need of ethics and the postulation of social responsibility by productions in the marketing region. The objective vary from the assessment of the current and up-and-coming ethical alarms, the explanation of certain models of real life exemplifying those apprehensions and the impact they have on individual consumers and the whole society. The analysis show most of the companies do not follow ethical means such as tobacco manufacturers; for this, there should be some new set of rules and regulations that must be followed by the industries for the wellbeing of consumers and society. Thus, there is an urgent need to follow certain paths that rely on good intentions and ethics to prosper the society and social values. This article also indicates all those factors that lead towards the unethical advertisement and manufacturing of different hazardous products.
Keywords: ethics; marketing ethics; emerging ethical issues; new directions and proposals